Mortality of employees of the United Kingdom Atomic Energy Authority, 1946–97. Issue 7 (18th June 2004) - Atkinson, W D; Law, D V; Bromley, K J; Inskip, H M
Abstract : Background: The workforce of the UK Atomic Energy Authority has been the subject of several previous epidemiological investigations. Aims: To detect and investigate associations between mortality rates and employment in a substantially increased cohort size and follow up extended to 1997. Methods and Results: The new cohort included 51 367 employees, of whom 10 249 were dead. Mortality rates for all workers were low compared to national rates, as were rates in radiation workers and for workers monitored for internal contamination. For radiation workers all cause mortality and all cancer mortality were significantly lower than for non-radiation workers. There was no overall trend of increasing mortality with radiation dose. There was little evidence of raised mortality from leukaemia. The association of prostatic cancer with radiation dose was much less significant than in previous reports. However, the relatively high mortality from uterine cancers among radiation workers remained, though the numbers were very small. The association was with endometrial rather than cervical cancer. Mortality from cancer of the pleura was high among radiation workers, but was not correlated with dose. Conclusion: Overall, radiation workers at UKAEA showed no excess mortality. The previously detected association of prostate cancer with high radiation dose may have been a statistical artefact or a risk associated with discontinued activities. Endometrial cancer occurred at higher rates in female radiation workers, but, because there was no correlation with dose, may well be due to something other than their radiation exposure. Cancer of the pleura in radiation workers was almost certainly related to past asbestos exposure.